Penundaan Stent pada Beban Trombus Tinggi: Sebuah Laporan Kasus - Kurniawan, Catur; Widito, Sasmojo; Putri, V.Y.S (RSUD Dr. Saiful Anwar Province of East Java, 2025)
Direct stent implantation is widely recommended for the management of patients who have acute myocardial infarction with ST-segment elevation. However, in situations where there is HTB in the affected artery, stenting may increase the risk of no flow phenomenon. Delaying stenting may reduce complications. A 45-year-old man presented with symptoms suggestive of acute right ventricular infarction that started 8 hours before admission. The patient underwent an echocardiogram which showed an ejection fraction of 36%. Pre-PCI pharmacotherapy was administered. Coronary angiography showed a grade IV occlusion in the mid-LAD branch as well as a thrombus in the mid-RCA with TIMI 2 flow. Thrombus aspiration and balloon inflation were performed, but HTB persisted. DS was decided, with additional Enoxaparin 0. 6 cc twice daily. Subsequent angiography after 34 hours, showed CAD in three coronary artery branches with the RCA still showing complete occlusion with HTB. A stent implantation procedure was performed in the mid-RCA segment The final result achieved was TIMI 3 blood flow, with no residual stenosis. HTB can also be diagnosed based on the TIMI thrombus risk classification. The main goal of deferred stenting is to minimize complications such as the slow-flow phenomenon of distal embolization. It is important to emphasize that a routine DS strategy has not shown clear benefit and is not recommended.